Pengaruh Latihan Imagery dan Konsentrasi Terhadap Ketepatan Free Throw Pada UKM Bola Basket Universitas Islam Indonesia - Muhammad Naufal Ramadhansyah (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2022)
Gross motor development is related and has an impact on the development of children, including children with mental disabilities. Children with mental disabilities will find it difficult to do movement activities that are too complicated, therefore traditional boy-boyan games are chosen to stimulate the interest of students with mental disabilities to want to do physical movements. Experimental research was chosen to test the effectiveness of traditional boy-boyan games on the gross motor skills of students with mental disabilities. The study was conducted on 15 students with mental disabilities at SLB Lab-UM Malang at the SDLB class V level. The research instrument used a 50-meter running test. The results of data analysis using a paired sample t-test obtained t value of 8.323 with a significance value of 0.00 (p<0.05). It can be concluded that there is a significant influence of boy-boyan play on improving gross motor movement skills in students with mental disabilities.